Are aids enough to empower: case of peatland Liberica Coffee farmer in Indonesia - Made Deviani Duaja; Elis Kartika; Johannes Johannes (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
Many agents have been involved to empower peatland farmers who cultivate Liberica Cofee. They have the same general purposes to save farming practices, but they have different programs and activities. Many agents involved had worried to blur focus and targets. Hence, the purpose of this study is to reveal empowering practice and performance. The study is located in Mekar Jaya village, the center of peatland Liberica Coffee, and used a qualitative method where field notes, observation, and in-depth interviews were used. Data collection was conducted in conjunction with the empowerment activities carried out by the research team in 2017-2019. The results showed the importance of empowering focus, coordination between groups, real participation of all groups and its members, and the need for local government intervention. Neglecting those will diminish the peatland farming environment function and farming roles to the farmer. In the future, the practice of empowerment will be more complex due to the global demands on the sustainability of peatlands increase. Hence, empowering could be started from farming improving, increasing productivity, and followed by increasing farmer's and group’s capacity to manage both on economics and environmental value of peatland farming.